Makrofauna Tanah di Bawah Pohon Jelutung Rawa (Dyera polyphylla Miq) Di Kebun Benih Semai (KBS) Universitas Palangka Raya - I.Y. Hutahean; Patricia Erosa Putir; Johanna Maria Rotinsulu; Penyang Penyang; Setiarno Setiarno (HUTAN TROPIKA, 2023)
Decomposition of organic matter in the soil is closely related to the presence of soil macrofauna. The better the process of organic matter decomposition, the better the physical and chemical properties of the soil, which, of course, will support soil fertility in a land area. This research aims to determine the presence of soil macrofauna under Jelutung Rawa trees (Dyera polyphylla Miq) in the peatland of the Seedling Garden (KBS) at Palangka Raya University. The research method was conducted by sampling soil macrofauna through Hand sorting method at 25 observation points and Pittfall Trap method at 20 observation points. The observed and identified soil macrofauna were examined in the laboratory using identification guidelines and literature on macrofauna types. The data were analyzed using the Shannon-Wiener species diversity index formula, the Margalef species richness index, the Pielou evenness index, and the calculation of species presence frequency. The research findings revealed 24 species, 23 genera, 20 families, 7 classes, and 3 phyla of soil macrofauna, with a total of 3,579 individuals. The values of the species diversity index (H'), species richness index (Dmg), evenness index (E), and the frequency of soil macrofauna presence (F) at KBS, Palangka Raya University were as follows: H' = 2.303325269 (moderate category), Dmg = 2.810760521 (moderate category), E = 0.724759677 (fairly even category), and frequency of presence, F = 80% - 100%.